Paeonia suffruticosa Andrews root extract ameliorates photoaging via regulating IRS1/PI3K/FOXO pathway - Liu, Junxi; Liu, Youyun; Wang, Feifei; Yuan, Yonglei; Ma, Hongyu; Qu, Liping (Frontiers in Pharmacology, 2025)
IntroductionThe root of Paeonia suffruticosa Andrews (P. suffruticosa Andr.), is a traditional Chinese medicine. Numerous studies have shown that it possesses anti-inflammatory, antioxidant, and anti-aging effects due to its rich content of bioactive compounds such as polyphenols and paeonol. Thus, it finds extensively applied in the fields of medicine and cosmetics. However, there are few reports on the photoprotective effects of P. suffruticosa Andr. root bark, this study aims to investigate its research in this area.MethodsThis study utilized P. suffruticosa Andr. root bark sourced from Kunming, Yunnan Province, China. The P. suffruticosa Andr. root extract (PSAE) was obtained using AB-8 resin. The photoprotective effect of PSAE was assessed using HaCaT cells, HFF cells, and a 3D Reconstructed Human full T-Skin™ model. Mechanistic investigations were performed using RT-qPCR, WB, IF, H&E staining, Masson’s trichrome staining and IHC staining. Finally, an assessment of the effects on humans was conducted.ResultsThe total phenolic content in the obtained PSAE was 48.9%. Antioxidant activity studies demonstrated that PSAE effectively inhibits DPPH radicals, superoxide anions, hydroxyl radicals, and ABTS radicals, while also enhancing the inhibition rates of collagenase and hyaluronidase. In vitro studies on photoaging resistance revealed that PSAE significantly reduced the UV-induced increases in reactive oxygen species (ROS) levels and senescence-associated β-galactosidase (SA-β-gal) activity. Mechanistic studies indicated that PSAE suppressed the overexpression of IRS1 and its downstream effectors, including PI3K, AKT, and mTOR induced by UV irradiation. A human efficacy assessment was conducted by evaluating parameters such as transepidermal water loss (TEWL), epidermal moisture content, roughness and elasticity, confirming the efficacy of PSAE in humans.DiscussionIn summary, PSAE attenuates UV-induced oxidative damage, genetic damage, and collagen degradation associated with photoaging by modulating the IRS/PI3K/FOXO signaling pathway. This study elucidated the mechanism through which PSAE, thereby providing strong support for its application in cosmetic anti-aging formulations.